Crime, the Criminal Justice System, and Socioeconomic Inequality - Magnus Lofstrom; Steven Raphael (Institute for the Study of Labor (IZA), 2016)
Crime rates in the United States have declined to historical lows since the early 1990s. Prison and jail incarceration rates as well as community correctional populations have increased greatly since the mid-1970s. Both of these developments have disproportionately impacted poor and minority communities. In this paper, we document these trends. We then present an assessment of whether the crime declines can be attributed to the massive expansion of the U.S. criminal justice system. We argue that the crime is certainly lower as results of this expansion and the crime rate in the early 1990s was likely a third lower than what they would have been absent changes in sentencing practices in the 1980s. However, there is little evidence of an impact of the further stiffening of sentences during the 1990s, a period when prison and other correctional populations expanded rapidly. Hence, the growth in criminal justice populations since 1990s have exacerbated socioeconomic inequality in the U.S. without generating much benefit in terms of lower crime rates.
Keywords: D3; D63; I3; 330; crime; criminal victimization; inequality; incarceration; prison